Curriculum reform in Lesotho: exploring the interface between environmental education and geography in selected schools - Raselimo, Mohaeka Gabriel (Rhodes University, Faculty of Education, Department of Education, 2012)
This study sought to explore the interface between environmental education (EE) and school geography with a view to understanding a process of curriculum reform in the context of Lesotho. The research was based on the curriculum reform process that was initiated by a Danish donor-funded project, known as the Lesotho Environmental Education Support Project (LEESP), which operated from 2001 to 2004. Driven by a sustainable development imperative, the project was intended to assist Lesotho in the implementation of local action for Agenda 21 by introducing environmental education into the formal education system. Deviating slightly from much published research on geographical and environmental education, which focuses on how geography contributes to environmental education, this study explored how the latter has shaped the former in terms of content and pedagogy. Using the lens of critical curriculum theory, I sought to understand the political nature of the curriculum and of curriculum change, focusing on the LEESP curriculum policy development, dissemination and implementation at classroom level. The study employed Bernstein's concepts of classification and framing to illuminate issues of power and control between discourses, and between teachers and learners. Operating within an interpretive qualitative research orientation, the study used a case study method focusing on five secondary/high schools in Lesotho. The data was generated through document analysis, interviews and classroom observations. The study examined the assumptions, values and ideologies underpinning environmental education curriculum intentions as reflected in LEESP documents. It also investigated the social process of conceptualising and disseminating environmental education to understand the challenges faced as education practitioners made sense of environmental education innovations in the specific contexts of Lesotho, and how these could possibly influence what happens at the classroom level. The analysis of the LEESP documents revealed that while there are many areas of synergy between the LEESP environmental education policy guidelines and the national education ideals in Lesotho, achievement of the transformational visions of action competence, which was the overarching concept in the reform process, would require major structural changes. The study also highlights issues of participation, contestations, tensions and contradictions associated with the conceptualisation and dissemination of environmental education. At implementation level, there is a disjuncture between environmental education policy intentions and practice. Geography teachers in the research schools generally understood the existence of environmental education in their schools in terms of environmental management. The findings also revealed that while there is generally a strong environmental dimension in geography content, as reflected in both curriculum materials and classroom practice, the subject still retains its disciplinary boundaries and makes little use of knowledge from other subjects or the everyday knowledge of the learners. Finally, it emerged that while the geography teachers in their rhetoric espoused learner-centred methods, in practice they generally employed traditional teacher-centred and book-centred methods. The study concludes that a lack of change in school geography in Lesotho, of the sort envisaged in LEESP, may be attributed to contextual and structural factors such as an overemphasis on examinations, and certain perceptions on the part of teachers and learners embedded in the history and culture of their society. A model of teacher professional development capable of supporting curriculum change is therefore proposed.
Keywords: Curriculum planning -- Lesotho; Curriculum change -- Lesotho; Educational evaluation -- Lesotho; Environmental education -- Study and teaching (Secondary) -- Lesotho; Geography -- Study and teaching (Secondary) -- Lesotho; Agenda 21 (Program)